Contraceptive experience and factors associated with desire for postpartum family planning among pregnant women of the nkongsamba health district, Littoral Region, Cameroon - Ajong, AB; Yakum, MN; Mangala, FN; Bekolo, CE; Agbor, VN; Waffo, LM; Kenfack, B (BioMed Central, 2025)
Background: The postpartum period remains a very important period during which contraceptive needs can be met and a significant reduction of maternal and foetal morbi-mortality achieved. This study aimed to evaluate past contraceptive experience and identify factors associated with the desire for postpartum family planning among women in late pregnancy. Methods: We conducted a cross-sectional survey from September 2020 to December 2021 in four major health facilities of the Nkongsamba Health District, Cameroon, and consecutively included all pregnant women in late pregnancy, who came for antenatal follow-up in these health facilities. Data were collected using a semi-structured interviewer-administered questionnaire. Multivariable logistic regression was used to estimate adjusted odds ratios (AORs) for the factors associated with desire for postpartum family planning. Two-tailed p-values < 0.05 were considered statistically significant. Results: Among the 1074 participants, 41.71% [95% CI: 38.78–44.70] reported a future desire for modern postpartum contraception. The self-reported prevalence of use of modern contraception in the past in the study population was 48.87% [95%CI: 45.86–51.88]. Only 17.64% [95%CI: 14.59–21.16] of women had adopted a modern contraceptive method other than the barrier methods in the past. Among pregnant women who had used modern contraception in the past, 11.50% [95%CI: 9.02–14.55] reported to have had their modern contraceptive experience with long-acting reversible contraceptives (LARCs). The prevalence of unintended pregnancy (current pregnancy) was 40.04% [37.15-43.00], with 11.55% being unwanted, and 28.49% mistimed. Compared to their respective counterparts, participants ≤ 30 years old (AOR = 0.71[0.52–0.99]), with monthly revenue below 100 thousand FCFA (AOR = 0.45[0.32–0.62]), who were single (AOR = 0.38[0.27–0.54]), had lower odds for desire of postpartum family planning. In contrast, women who were Christians (AOR = 2.13[1.27–3.58]), with a history of use of modern contraception before conception (AOR = 2.80[2.02–3.90]), and had a current unintended term pregnancy had higher odds of desiring postpartum contraception (AOR = 2.91[2.13–3.99]). Conclusion: The desire for postpartum family planning is still low among pregnant women. This desire for postpartum family planning depends on sociodemographic factors and past contraceptive practices.